Synthesis of highly porous poly(tert-butyl acrylate)-b-polysulfone-b-poly(tert-butyl acrylate) asymmetric membranes - Xie, Y.; Moreno, N.; Calo, Victor; Cheng, H.; Hong, P.; Sougrat, R.; Behzad, A.; Tayouo, R.; Nunes, S. (R S C Publications, 2016)
For the first time, self-assembly and non-solvent induced phase separation was applied to polysulfone-based linear block copolymers, reaching mechanical stability much higher than other block copolymer membranes used in this method, which were mainly based on polystyrene blocks. Poly(tert-butyl acrylate)-b-polysulfone-b-poly(tert-butyl acrylate) (PtBA30k-b-PSU14k-b-PtBA30k) with a low polydispersity of 1.4 was synthesized by combining step-growth condensation and RAFT polymerization. Various advanced electron microscopies revealed that PtBA30k-b-PSU14k-b-PtBA30k assembles into worm-like cylindrical micelles in DMAc and adopts a "flower-like" arrangement with the PSU central block forming the shell. Computational modeling described the mechanism of micelle formation and morphological transition. Asymmetric nanostructured membranes were obtained with a highly porous interconnected skin layer and a sublayer with finger-like macrovoids. Ultrafiltration tests confirmed a water permeance of 555 L m-2 h-1 bar-1 with a molecular weight cut-off of 28 kg mol-1. PtBA segments on the membrane surface were then hydrolyzed and complexed with metals, leading to cross-linking and enhancement of antibacterial capability.